Наукова кар'єра Миколи Костомарова - Шандра, В. (Історіографічні дослідження в Україні, 2018)
З’ясовано чинники, котрі впливали на кар’єру Миколи Костомарова. Серед них – соціальне походження, здібності, лояльне ставлення
до політики верховної влади Російської імперії. Названо законодавчі
акти, якими держава регулювала наукові здобутки вчених, та встановлено, як вони сприяли професійному зростанню відомого історика.
Звернуто увагу на державні посади, які обіймав учений, та які мав
чини, і чому відмовився від статської служби, віддавши перевагу
науковій і викладацькій діяльності. Визначено, що відсутність політичної, а почасти й наукової свободи стала тим фактором, який
стримував наукову кар’єру М. І. Костомарова. Історик відмовився від
формалізованих принципів і розірвав відносини з державною владою.
Громадська позиція вченого сприяла тому, що він став духовним
лідером українського руху. The report examines the factors that influenced Mykola Kostomarov's
career were revealed. Among them, social origin, ability, loyalty to the
policy of the supreme power of the Russian Empire. Named the legislative
acts that the state regulated the scientific achievements of scientists and
established how they promoted the professional growth of the scientist. It is
paid attention to what official positions occupy the historian and who had
ranks and why he refused the state service, giving preference to scientific
activity. It is paid attention to the official positions occupied by the
historian and who had ranks and why they refused to state service, giving
preference to scientific activity. It has been determined that the lack of
political, but partly, scientific freedom has become the factor that restrained
Kostomarov's scientific career. The historian abandoned the formalized
principles and severed relations with the state authorities. His public
position contributed to the fact that the historian became the spiritual
leader of the Ukrainian movement.